On multicarrier signal transmission for high-voltage power lines - Pighi, R.; Raheli, R. (2005 International Symposium on Power Line Communications and Its Applications : ISPLC 2005 : April 6-8, 2005, Vancouver, Canada, 2005)
Orthogonal frequency division multiplexing (OFDM), as a type of multicarrier modulation, is becoming one of the preferred communication schemes to achieve reliable high-rate data transmission. In this paper, we propose a multicarrier signal transmission system to be applied in a high-voltage power line scenario and we demonstrate the gain of the proposed scheme with respect to a single carrier power line modem in terms of achievable bit-rate for a given quality of service requirement.